2023
DOI: 10.1093/evlett/qrac003
|View full text |Cite
|
Sign up to set email alerts
|

The immediate effects of polyploidization ofSpirodela polyrhizachange in a strain-specific way along environmental gradients

Abstract: The immediate effects of plant polyploidization are well characterized and it is generally accepted that these morphological, physiological, developmental, and phenological changes contribute to polyploid establishment. Studies on the environmental dependence of the immediate effects of whole-genome duplication (WGD) are, however, scarce but suggest that these immediate effects are altered by stressful conditions. As polyploid establishment seems to be associated with environmental disturbance, the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 80 publications
3
20
2
Order By: Relevance
“…Recent work suggests that, in some instances, cytotypes can perceive the same environmental state differently (Bafort et al 2023). Hence, instead of modeling explicit directional competition among cytotypes and their community members, our study allows divergence in niche among cytotypes to be driven by the environment.…”
Section: Coexistencementioning
confidence: 99%
See 3 more Smart Citations
“…Recent work suggests that, in some instances, cytotypes can perceive the same environmental state differently (Bafort et al 2023). Hence, instead of modeling explicit directional competition among cytotypes and their community members, our study allows divergence in niche among cytotypes to be driven by the environment.…”
Section: Coexistencementioning
confidence: 99%
“…Similarly, in low environmental variance, we identified shifts in competitive ability among model replicates. In relation to environmental variation, the growth rate and carrying capacity of tetraploid Spirodela polyrhiza (Araceae) were lower than those of cooccurring diploids (Anneberg et al 2023); however, a tetraploid fitness advantage was identified in saline environments (Bafort et al, 2023). Despite the competitive disadvantage of S. polyrhiza tetraploids compared to diploids in most treatments, tetraploids were found to invest more than their diploid progenitors into future growth through dormant propagules (Anneberg et al, 2023) environments.…”
Section: Environmental Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…The most appropriate fitness comparison is to be made at the population level, where diploid and polyploid growth both within generations and reproduction among generations contribute to population fitness (e.g., Selmecki et al, 2015;Anneberg et al, 2023). Recurrent formation of polyploids from genetically different diploids is a common phenomenon in nature (Soltis & Soltis, 1999;Kolář et al, 2017) and could lead to variation in stress tolerance even when polyploidy involves one parental genome (autopolyploidy) rather than two genomes (allopolyploidy) (e.g., Wei et al, 2019;Bafort et al, 2023;Mattingly & Hovick, 2023). This variation in stress tolerance may ultimately determine the probability of polyploid establishment under novel or stressful conditions (Soltis & Soltis, 1999;Van Drunen & Johnson, 2022).…”
Section: Introductionmentioning
confidence: 99%